A política educacional para EJA – educação de jovens e adultos: o CEEBJA – centro estadual de educação básica para jovens e adultos – professora Joaquina Mattos Branco – Cascavel – Paraná - Peletti, José Armando (2016)
We seek for understanding the history and objectives of the creation of this school. It was object of analysis of matriculation books, PPP – Pedagogical Political Project – of the school, apt legislation, CONAE reports, of ENEJAS of the EJA FORUNS, and of the CONFINTEAS and also, reports that were produced by the own MEC and SEED/PR about the EJA theme. The aim was to analyze the public policy in Young and Adults Education – EJA, implemented in Paraná stem from the creation of CESVEL (Supplementary Studies Center), and today named CEEBJA – State Center for Young and Adults Basic Education - Teacher Joaquina Mattos Branco, Cascavel, Paraná, to understand if the historical demand created, a demand of Young, adult and old people needing a different education method, according to their ages, their time, profiles and prospect, is being met by a education method proposed and developed, in Paraná specifically in CEEBJA, therefore providing the verification of the effectiveness of the policy adopted for the access and permanency to a population that haven‟t had an opportunity to attend the ordinary school in the so called suitable age. This way, it was analyzed the public policy in Young and Adults Education – EJA, implemented in Paraná since 1984, specifically in CEEBJA, considering the way it‟s organized, the students‟ profile that seek for it, the historical need for its existence and the offer of this teaching modality. It could be seen that, by the own reports of the public organs and the social organisms that discuss the education, mainly EJA, that since the beginning of this school, proposed to attend those ones who couldn‟t attend the ordinary school, it was little encouraged. Has it improved? Some points have, but many of them are still out of schools, at an „old‟ age, with few years at school or not even literate.